A study on motivated consumer innovativeness in robotic golf caddies - Hwang, Jinsoo; Song, Sujin; Park, Sungbeen (Institute of Advanced Engineering and Science, 2026)
The current study examined the antecedents and consequences of image in the field of robotic golf caddy. Data were collected from 393 golfers in Korea. The data analysis revealed that functionally, hedonically, and cognitively motivated consumer innovativeness are the key factors that affect image. It was also found that image helps in regard to enhancing desire, and then it positively affects intentions to use and WOM intention. Perceived price unfairness of caddy fees additionally moderated the relationship between functionally motivated consumer innovativeness and image. This study is significant from a theoretical perspective as it is the first to identify consumer motivations in the field of robotic golf caddies. From a practical standpoint, the findings offer important implications for the development of marketing strategies for robotic golf caddies, which are currently at the commercialization stage.